Rapid physiological colouration change is a challenge - but not a hindrance - to successful photo identification of giant sunfish (Mola alexandrini, Molidae) - Nyegaard, Marianne; Karmy, Jennifer; McBride, Lauren; Thys, Tierney M.; Welly, Marthen; Djohani, Rili (Frontiers in Marine Science, 2023)
Photo ID is a common tool in ecology, but has not previously been attempted for the ocean sunfishes (Mola spp., Molidae; ‘molids’). The technique, based on body patterns, could potentially be informative for studying the seasonal occurrence of giant sunfish (Mola alexandrini) on the Bali reefs (Indonesia), where this species is an important drawcard for the local SCUBA diving tourism. However, molids are capable of rapid physiological colouration change, which may complicate the application of the method. Our study aimed to determine if photo ID is nevertheless achievable and informative. To test this, we created the citizen-science platform ‘Match My Mola’ for crowd-sourcing imagery (photos and video) of M. alexandrini in Bali, and undertook trial matching (n=1,098 submissions). The submitted imagery revealed a wide range of pattern clarity, from fish with no pattern to bold displays. Video confirmed physiological colouration change can occur in seconds in this species from low to high contrast, and cause individuals to look very different between moments. However, individual patterns appear to be stable although at least some parts can become inconspicuous during low contrast displays. Despite of this, photo ID is possible, including in some instances, where only partial patterns are visible on one image compared with another. However, true negatives (confirming two fish are not the same) can be challenging. Most identified matches were of fish photographed by different divers on the same day. Only a small number (n=9) were found with resighting durations ≥1 day (1 – 2,652 days). These matches demonstrate that at least some individuals return to the same reefs both within and between seasons, with the resighting duration of 7.2 years constituting the longest known example of molid site fidelity. Comparing body morphology between resightings of > 1 year (n=6) revealed limited indications of growth, contradicting the current understanding of rapid growth in captive molids (Mola mola), and highlighting the knowledge gap regarding growth in the wild. Continued photo ID in the Bali area could provide valuable complementary information to future growth studies using other methods as well as provide further insights into molid site fidelity.